Pengaruh Moral Sensitivity, Transparansi dan Akuntabilitas Terhadap Pencegahan Fraud Dalam Pengelolaan Alokasi Dana Desa - Firda Aulia; Sofyan Syamsuddin; Sahrir Sahrir (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to determine the effect of moral sensitivity, transparency and accountability on fraud prevention in managing village fund allocations in the Masamba District, South Sulawesi. The method used in this research is quantitative. The population of this study were all village officials in Masamba sub-district, Luwu-north district, South Sulawesi province. The sample for this study were 116 village officials, obtained using a non-probability sampling technique, namely saturated sampling. While data analysis is utilized to assess research hypotheses in order to formulate study outcomes by statistical testing using SPSS software, this type of data empolys primary data by distributing questionnaires to respondents. The results of the study show that moral sensitivity has no effect on fraud prevention in managing village fund allocations. This study also found that transparency and accountability have an influence on preventing fraud in managing village fund allocations. These findings help to gain insight regarding special attention to approaches that can minimize the occurrence of fraud in the management of village funds, namely morale and transparency and accountability.